Relationship between Age, Gender and ABO Blood Groups in Childhoods Cancer - Yaseen, Orass Khalis (Diyala Journal of Medicine, 2019)
Background: Cancer also known as a malignant tumor or malignant neoplasm, is a group of diseases involving abnormal cell growth with the potential to invade or spread to other parts of the body. Not all tumors are cancerous; benign tumors do not spread to other parts of the body. Many studies were summarized that strong correlation between the ABO groups and cancer. Types of childhood leukemia are more commune than other types of cancer. Objective: To study the relationship between cancer and different parameters such as age, gender and ABO groups type in children. Material and Methods: The study was conducted at cancer center in Al-Batool teaching hospital for maternity and children in Baquba city, during the period from August 2014 till July 2015, ages ranged between (1-15) year, were organized the patients by information form, diagram paper of development the disease, treatment program and other chemotherapy. Result: A number was one hundred cases with different types of cancer, the results showed that high percentage (65%) of patients with cancer was males compare with females (35%) significance difference was noticed (p<0.05). Most cases (44%) in children was born O type group compare than other types of blood groups, (5%) had type AB, (24%) had type B and (27%) had type A. high percent of disease occur at age (1-5) year recorded differential significance (p<0.05). Conclusion: Cancer rate was very high in males and in blood group type O, according to age most cases recorded in age group (1-5) years.